Interaction effect of Nd:YAG laser and universal adhesive system for dentin sealing - Penha, Karla-Janilee-de Souza; Torres, Carlos-Rocha-Gomes [UNESP]; Tavarez, Rudys-Rodolfo-De Jesus; Firoozmand, Leily-Macedo (Medicina Oral, S.L., 2020)
Background: To evaluate the influence of the association of the universal adhesive system to different energy densities of the Nd:YAG laser on the hydraulic conductance of dentin. Material and Methods: Fifty bovine dentin discs were made. The samples were stratified into four groups (n = 10) according to the treatment performed; SBU- Adper Single Bond Universal (3M ESPE), SBU_60 - SBU associated with the Nd:YAG laser (60mJ, 10Hz, 0.6W - 47.77 J / cm²), SBU_80 - SBU associated with the Nd:YAG laser (80mJ, 10Hz, 0.8 W - 63.69 J / cm2) and C – dentin without treatment (smear layer). Hydraulic conductance measurements were taken 24 hours after the treatments (HC1) and after erosive challenge (HC2). Scanning electron microscopy (SEM) and energy dispersive X-ray spectrometry (EDX) helped to visualize the dentin after the different treatments. Scheffe and Games-Howell statistical tests were used to analyze hydraulic conductance (α = 0.05). Results: The treated dentin (SBU, SBU_60, and SBU_80) reduced HC1 when compared to dentin with smear layer (C) (p < 0.001). The erosive challenge has increased HC2 in SBU_60 and C (p < 0.001), and did not promote a significant difference in SBU_80 and SBU. The SEM / EDX analyzes showed an irregular and semi-permeable barrier on the surfaces of the treated dentin. Conclusions: The association of universal adhesive with Nd:YAG can be an effective alternative for the occlusion of dentinal tubules, whereas higher energy per pulse Nd:YAG (SBU_80) can increase the resistance to permeability when exposed to the erosive challenge.
Keywords: adhesives; Dentin; Nd:YAG Laser; permeability of dentin